An analysis of the use of the video game with the experience of cinematic convergence in the community of fans and players – The case of Hogwarts Mystery - Vieira, Maria Júlia Limeira (Seven Editora, 2023)
In 1997 that the Harry Potter saga at the end of its first book released managed to attract fans from all over the world there several ways to consume the content created by the writer J. K. Rowling were created, bringing to the media and the entertainment industry an object of study comprehensive in its multiple expressions within the culture of convergence. In addition to the books and movies, Harry Potter fans were able to learn about interactive content that brought them closer to the work. An example of this interactivity is the video games created to bring the user an experience closer to reality, thus creating a greater empathy between the player and the work. In this context, this study aims to analyze the video game available for mobile, the Hogwarts Mystery, about the culture of convergence, bringing the fan and the user as a source of inspiration for the acceptance, representation, and continuity of the game in the community of fans. This analysis will focus on understanding what are the strategies used by the creator of the video game to enhance the active participation of fans of the saga in this game through the culture of convergence thus analyzing the result of acceptance of use by players. DOI:https://doi.org/10.56238/devopinterscie-125